Design and synthesis of 3D porous diamondoid frameworks by cocrystallization - Tothadi, Srinu; Little, Marc A.; Hasell, Tom; Briggs, Michel E.; Chong, Samantha Y.; Cooper, Andrew I. (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: cocrystals; crystal engineering; Porous Organic Cages

Modular assembly of porous organic cage crystals: isoreticular quasiracemates and ternary co-crystal - Tothadi, Srinu; Little, Marc A; Hasell, Tom; Briggs, Michael E.; Chong, Samantha Y.; Liu, Ming; Cooper, Andrew I. (CrystEngComm, 2017)
Small changes in molecular structure and crystallisation conditions can have a profound effect on the crystal packing of molecules. Increasing the system complexity-for example, by introducing multiple components-greatly increases the number of potential outcomes. Hence, the rational design of porous cocrystals with multiple components is challenging. Here, we report a family of isoreticular quasiracemate crystalline phases for porous organic cages, FT-RCC3-R center dot CCX-S (where X = 1, 2, or 4), that were prepared in a modular and predictable fashion. By using directional intermolecular interactions between cages, we were able to prepare a rare ternary co-crystal, (CC3-S(0.5)CC4-S-0.5)center dot(CC13-S(0.5)CC3-S(0.25)CC4-S-0.25).
Keywords: cocrystals; Frameworks; Gas-chromatography; Halogen Bonds; Hydrogen-bonds; Molecular Cage; Nanoparticles; Pores; porosity; Separation